Analysis of Air and Water Quality at Coal Harbor in Muaro Jambi Regency - Wahyu Prasetyo Agus Susanto; Mulya Gusman; Indang Dewata; Eri Barlian; Nur Efendi (Jurnal Penelitian Pendidikan IPA, 2023)
Secondary data obtained from the Safety, Health and Environment Department of PT. Winner Prima Sekata (PT. WPS) in Kemingking Dalam Village, Taman Rajo District, Muaro Jambi Regency, in 2022 it was discovered that there were cases of Acute respiratory infections (ARI). Therefore, a study was carried out regarding the analysis of air quality and water quality at the coal port location in Muaro Jambi Regency to determine the extent of the environmental impacts resulting from coal loading and unloading and stockpile activities at the Talang Duku port, Jambi Province. The research was conducted using quantitative survey and descriptive methods. Data analysis is quantitative in nature with the aim of testing predetermined hypotheses. Dust measurement results obtained between 7.98 - 10.00 mg/m3, The allowable dust threshold value is in accordance with the Minister of Manpower Circular Number. SE.01/MEN/1997 concerning the NAB of Chemicals in Workplace Air is 0.9 mg/m. So the dust level in the Muaro Jambi coal port working area exceeds the quality standards set by the Minister of Manpower. Results of calculating the output water pollution index pH and TSS at the PT Outlet point. The WPS of port locations in the period March – June 2023 in each month has a Pij value of 1.08, which means the average pH and TSS value of output water from PT. WPS is at status 1.0 < 1.09 < 5.0 with the description Lightly Polluted. Based on processing with SPSS version 27 using the One way Anova test, it was found that Fcount then H0 was rejected.